Recycling of biomass and coal fly ash as cement replacement material and its effect on hydration and carbonation of concrete - Teixeira, Elisabete Rodrigues (2019)
The construction sector has been using supplementary materials in concrete production worldwide, such as coal fly ash. Nowadays, several sub/products or wastes have been studied to be incorporated in construction materials, and one of those wastes is biomass fly ash. However, using high volumes of these materials has some drawbacks, one of them being carbonation. In order to understand phenomena such as this, it is important to study the interaction between the additions and hydration of cement. This paper focuses on the study of hydration and carbonation of cementitious pastes containing biomass fly ash and/ or coal fly ash by using thermogravimetric analysis and X-ray diffraction analysis and by accelerated carbonation tests. BFA present different chemical and mineralogical composition than CFA. The results show that incorporating biomass fly ash into construction materials has a similar carbonation behaviour to coal fly ash. Biomass fly ash seems to give some extra alkalinity to the mixtures, and this may present benefits to the construction materials and for the ash management.